FEATURES INTEGRATED APPLICATION OF THE FRAX MODEL WITH ULTRASOUND DENSITOMETRY - Myhal, Viktoriia; Kazakov, Yurii; Chekalina, Nataliia (Sworld-Us Conference proceedings, 2023)
The work examines the features of osteodysmetabolic syndrome during menopause. The complex application of ultrasound densitometry with the Ukrainianized FRAX model will allow to identify risk groups for the development of a decrease in bone mineral densit